Eating in an extreme environment: diet of the European hare (Lepus europaeus) on Vesuvius. Issue 1 (31st December 2022) - Buglione, M.; de Filippo, G.; Conti, P.; Fulgione, D.
Abstract: The European hare ( Lepus europaeus ) is cosmopolitan species, living in a variety of habitats and showing a diversified diet, that has been described mainly from agricultural meadows and crops, with little information available for extreme environments. Here, we describe, for the first time, the diet of the European hare from Mount Vesuvius, using DNA metabarcoding and high-throughput sequencing on DNA extracted from faecal pellets, a proxy for a population living in a volcanic environment. The DNA from pellets was first genetically assigned to European hare using high-resolution melting analysis. The diet of the hare on Vesuvius is mainly composed of herbaceous species belonging to Fabaceae (86.26% of total diet). The most frequent plant items ingested by the species are Galega officinalis and Lupinus angustifolius (67.10% of total diet), although these are detected only sporadically in the study area. Indeed, the spectrum of available plants also includes other easily accessible wild (i.e. Lolium sp., Bromus sp., Rumex sp.) and cultivated (i.e. Solanum lycopersicum, Cucumis melo, Pisum sativum ) plant items, found only in traces in the diet of the hares. Our contribution adds information on the trophic ecology of the European hare, exploring its ability to live in an extreme environment. This could be useful to set a management strategy for conservation of the species, which is ecologically relevant on Vesuvius as prey for birds and mammals, as well as a vegetation modulator via selective grazing by endozoochory. Furthermore, our study represents the latest information on the diet of the hare living in an environment that no longer exists: an extensive fire destroyed about 80% of the woody area after our sampling. The post-fire regrowth is transforming the original environment and consequently the trophic availability for the European hare. Key policy highlights: Conservation of biodiversity in a national park Ecosystem service of the European hare Management of a Lagomorpha game species